2023
DOI: 10.3389/fpsyt.2023.1134396
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on emotional and behavioral problems of children with autism spectrum disorder and developmental delay aged 1–6 years in China

Abstract: IntroductionThe COVID-19 pandemic outbreak have caused increased levels of emotional and behavioral problems, particularly among people with pre-existing mental health conditions. Young individuals with autism spectrum disorders (ASD) and developmental delay (DD) are particularly at risk due to their vulnerability. The purpose of this study was to look into the different effects of the COVID-19 pandemic on 1–6-year-old children with ASD and DD.MethodsParents and guardians of children with ASD completed an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Thirdly, previous psychiatric disorders, especially neurodevelopmental disorders, are a frequent comorbidity in subjects who do an ED admission for psychological fragility. Moreover, subjects with ASD and ADHD showed worrying symptomatology during the first phases of COVID-19 pandemic ( Giallonardo et al, 2021 ; Zhao et al, 2023 ), thus suggesting that a cluster of subjects in our sample could have a neurodevelopmental disorder and that this could be an important variable that should have been considered in our analyses. By the way, due to the retrospective nature of this study, it was impossible including a cluster analysis on these subjects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thirdly, previous psychiatric disorders, especially neurodevelopmental disorders, are a frequent comorbidity in subjects who do an ED admission for psychological fragility. Moreover, subjects with ASD and ADHD showed worrying symptomatology during the first phases of COVID-19 pandemic ( Giallonardo et al, 2021 ; Zhao et al, 2023 ), thus suggesting that a cluster of subjects in our sample could have a neurodevelopmental disorder and that this could be an important variable that should have been considered in our analyses. By the way, due to the retrospective nature of this study, it was impossible including a cluster analysis on these subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Those with ADHD exhibited an increased prevalence of exaggerated startle responses, difficulties in waking up, angry moods, and COVID-19-related fears compared to typically developing children and adolescents ( Giallonardo et al, 2021 ). Another study also revealed a higher likelihood of negative emotional and behavioral changes in children aged 1–6 years with autism spectrum disorder (ASD) ( Zhao et al, 2023 ). Mental problems caused by the COVID-19 pandemic in adolescents may have serious and lasting effects, leading to poor mental and physical health conditions ( Jones et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition can cause alterations such as apoptosis, blocked cell division, cell aging, and death [43]. Telomere shortening in the brain has been linked to aging and aging-related diseases in observational studies, including AD, Parkinson's disease, schizophrenia among others [44][45][46][47][48][49][50][51][52]. Notably, individuals with AD had a higher rate of leukocyte telomere shortening per year compared to healthy individuals and those with MCI [53].…”
Section: Telomere Length and Cognitive Functionmentioning
confidence: 99%
“…According to the article, children with developmental disabilities, especially ASD, faced emotional challenges during COVID-19. Online support was found to be ineffective for providing educational intervention to children with ASD in China (Zhao et al, 2023). In this study, the authors investigated challenges faced by 50 children (aged 6 to 10 years old) diagnosed with ASD, ADHD, and DLD.…”
Section: Related Workmentioning
confidence: 99%